Soil health practices have different outcomes depending on local soil conditions - Scott M. Devine (California Agriculture, 2022)
The amount of soil organic matter is a critical indicator of soil health. Applying compost or manure, growing cover crops, reducing tillage, and increasing crop diversity may increase soil organic matter. However, soil organic matter can vary dramatically in different environments, regardless of management practices. This calls for a framework to recommend place-based soil health practices and evaluate their outcomes. We used a new framework that groups soil survey data into seven regions in California's Central Valley and Central Coast. These regions either have performance limitations, such as root restrictive horizons, salinity, and shrink-swell behavior, or have relatively homogeneous, coarse-to-loamy soils ideal for agriculture. These inherent conditions affect a soil's response to practices designed to improve soil health. Looking at vineyards as an example, we find significant soil organic matter contrasts between soil health regions but not among contrasting management approaches within a given region. We also show that conservation practices improve or help maintain soil health in several long-term experiments, but inherent soil properties and types of cropping systems affect outcomes.